Improving the Evaluation of Alveolar Bone Grafts with Cone Beam Computerized Tomography. (January 2016) - Marques De Moura, Pollyana; Hallac, Rami; Kane, Alex; Seaward, James
Objective: Cone Beam computed tomography (CBCT) is used increasingly as a replacement for periapical x-rays when evaluating alveolar bone grafting. The manufacturer's standard settings for dental imaging may not, however, represent the optimal settings for evaluating postoperative alveolar bone grafts. We examined the influence of exposure parameters on CBCT image quality to optimize the quality of CBCT images while reducing the radiation dose to the minimum level necessary to obtain adequate images. Methods: A defect was created in a cadaver head to simulate an alveolar cleft, and the area was filled with a synthetic material to simulate an alveolar bone graft. Serial CBCT scans were acquired, systematically varying tube voltage and tube current settings from 72 to 96kV and 3 to 12mA. Region of interest analysis was undertaken, and image quality was evaluated by comparing the ratios of native alveolar bone to soft tissue and the ratios of synthetic bone graft to soft tissue and by assessing image noise. Results: Twenty-one CBCT data sets were obtained. Reducing tube voltage (kV) resulted in increased contrast ratio between bone and soft tissue and between synthetic bone graft and soft tissue, with maximal contrast at values of 76 kV/11 mA, 72 kV/12 mA, and 72 kV/11 mA. Of these, the setting with lowest image noise was 76 kV/11 mA. This setting also resulted in a radiation dose of less than half of the manufacturer's recommended settings for the same scan volume. Conclusions: There is potential to improve CBCT image quality significantly while dramatically reducing the radiation dose during postoperative examinations for alveolar bone grafting in patients with cleft lip and palate.